Examining transformational leadership practices of primary school principals in the Musandam Governorate in the Sultanate of Oman (Arabic) - Al shehhi, Nabila Abdullah Ali; Badrasawi, Kamal J I (IIUM Press, International Islamic University Malaysia, 2020)
The study explored teachers’ perceptions of transformational leadership practiced by primary school principals in the Musandam Governorate in the Sultanate of Oman. The population included all teachers (N = 256) teaching Grades 5 to 12 in all primary schools in the governorate. A stratified random sample of 154 teachers (100 male and 54 female) was drawn from the population. Data were collected using a 47 item-questionnaire administered in a cross-sectional survey. Descriptive and inferential statistics were used in the data analysis. The results showed that teachers perceived transformational leadership practices to be prevalent among the school principals. Moreover, no statistically significant differences were found in the teachers’ perceptions of the principals’ transformational leadership practices by gender, academic qualification and years of experience. Pursuant to the findings, this study urges the Omani Ministry of Education to continue their effort in training principals on transformational leadership practices, and make use of the principals’ expertise to help other school principals with less experience in this type of school management. To obtain a greater depth of understanding regarding transformational leadership among school principals, qualitative research is, therefore, recommended